Pemanfaatan Canva Sebagai Aplikasi Dalam Penyusunan Media Ajar Untuk Tutor Kejar Paket C di PKBM Anggrek Bulan, Banyuwangi - Mardiani, Desika Putri; Riyanto, Yatim; Johny Artha, I Ketut Atmaja; Mardliyah, Sjafiatul; Siswanto, Heru; Nugroho, Rivo (Jurnal Dedikasi Madani, 2025)
The purpose of this service is to provide a learning experience for tutors of Study Group of Packages C at PKBM Anggrek Bulan in preparing teaching materials because so far the tutors have not maximally used this application in the learning process. The activity was carried out in the form of a training workshop with 25 very enthusiastic participants. The results of this activity are that there is high enthusiasm from the trainees in participating in the workshop which can be seen from their enthusiasm in practicing using the Canva application to compile and design teaching materials attractively, quickly, and creatively. There was an increase in knowledge, attitudes, and skills after attending this workshop. It can be concluded that this workshop yielded positive results on the skills of the tutors of package C in developing their teaching materials.